Reliability estimation for the randomly censored pareto distribution - Mahmoud M. Smadi; Saiful Islam Ansari; Ahmed A. Jaradat (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Widespread applications of random censoring in life testing experiments to estimate reliability of engineering products or systems are avialable. Different parametric statistical models such as exponential, Rayleigh, Weibull and Maxwell distributions are used under random censoring scheme. In this paper, random censoring under Pareto distribution is considered. The maximum likelihood estimators (MLE’s) of the model parameters and survival function were derived along with Fisher information matrix and asymptotic confidence intervals. A simulation study was performed to observe the behavior of the MLE’s. The simulation results showed that the bias and MSE were reasonably small in all cases.